2009
DOI: 10.21273/jashs.134.6.667
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of End Products in Source Leaves Affects Photosynthetic Rate in Peach via Alteration of Stomatal Conductance and Photosynthetic Efficiency

Abstract: In ‘Beijing 24’ peach [Prunus persica (L.) Batch] trees, a series of source leaves with differing levels of end products were created by retaining fruit (“+fruit”), removing fruit (“−fruit”), or reducing the light period. To alter the light period, leaves were covered with a bag made of brown inner paper and outer silver paper, which was then removed at different times the next day. The highest level of end products were obtained by fruit removal, while reducing the light per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
1
14
2
Order By: Relevance
“…Lettuce plants might have low sink demand owing to low developmental progress at later growth stages. This hypothesis is supported by Cheng et al [60], who found lower carbohydrate contents at later growth stages in peach.…”
Section: Red Light Increase Carbohydrate Contentssupporting
confidence: 58%
See 2 more Smart Citations
“…Lettuce plants might have low sink demand owing to low developmental progress at later growth stages. This hypothesis is supported by Cheng et al [60], who found lower carbohydrate contents at later growth stages in peach.…”
Section: Red Light Increase Carbohydrate Contentssupporting
confidence: 58%
“…In the current study, the starch concentration was higher at 20 DAT, whilst the concentration of soluble sugars had a declining trend at 20 DAT (Figure 4). Cheng et al [60] noticed that plant sourcesink relationships influence the carbohydrate allocation during plant growth. Sucrose is the primary carbohydrate that is translocated from source to sink tissues.…”
Section: Red Light Increase Carbohydrate Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies, including our study on peaches and apples did not show a relationship between assimilate accumulation and the reduction of net photosynthetic rate ( P n ) under low sink demand [4], [6][8], [11], [15]. The mechanism by which low sink demand affects photosynthesis is still unclear.…”
Section: Introductioncontrasting
confidence: 55%
“…Generally, low sugar status enhances photosynthesis, reserve mobilization and export, whereas high sugar content promotes growth and carbohydrate storage (Koch, 1996;Roll et al, 2002). In peach, removing fruit from tree increased the level of end products of photosynthesis and decreased the net photosynthetic rate (P n ), maximal quantum yield of photosystem II (Fv/Fm) and actual photochemical efficiency of photosystem II (FPSII) (Cheng et al, 2009). Therefore, the initial cleavage of sucrose in sink organs plays an important role in carbon partitioning and allocation.…”
Section: Discussionmentioning
confidence: 99%